Correction of DIAL stratospheric ozone measurements in the presence of Pinatubo aerosols - Fenn, Marta A.; Ismail, Syed; Browell, Edward V.; Butler, Carolyn F. (1992)
NASA Langley's airborne lidar system measured aerosol and ozone distributions in the stratosphere from Jan. - Mar. 1992 as part of the Airborne Arctic Stratospheric expedition (AASE-2). The eruption of Mount Pinatubo in Jun. 1991 has increased the aerosol burden of the stratosphere and thereby increased the importance of applying an aerosol correction to the ozone measurements. The correction relies on a Bernoulli solution to derive a backscatter correction to the differential absorption lidar (DIAL) returns at two wavelengths in the ultraviolet spectral region (lambda(sub on) = 301.5 nm, lambda(sub off) = 310.87 nm) as described in earlier works. This paper discusses how the parameters for the correction were optimized for application to the AASE-2 data set.